Nutrição mineral do mamoeiro (Carica papaya L.): III - sintomatologia de carências nutricionais - Cunha, Rubens José Pietsch [UNESP]; Haag, Henrique Paulo (Universidade de São Paulo (USP), Escola Superior de Agricultura, 1980)
Objetivando caracterizar as deficiências de N, P, K, Ca, Mg e S em mamoeiro (Carica papaya L.) em condições de casa de vegetação e soluções nutritivas, desenvolveu-se o presente trabalho. Os autores descrevem os sintomas de carência dos macronutrientes, com exceção do enxofre, cujas plantas que receberam o tratamento deficiente neste nutriente, não mostraram sintomas, provavelmente por contaminação externa. Os níveis analíticos encontrados em folhas sadias e desnutridas, expressos em função da matéria seca foram: N-4,24% e 3,61%; P-0,52% e 0,14%; K-3,81% e 1,36%; Ca-1,29% e 0,28%; Mg-0,65 e 0,17%.

The purpose of the present research was to characterize symptoms of macronutrient deficiency of papaya trees growing on nutrient solution under greenhouse conditions. It was possible to characterize and distinguish deficiency symptoms for all macronutrients, except for sulfur. Nitrogen deficiency showed off a clorosis of the basal leaves. Phosphorus deficiency was characterized as a partial clorosis of the intermediate leaf blades and potassium as a marginal clorosis and necrossis og young and old leaf edges. Magnesium deficiency was characterized as a clorotic mottle of young leaves and an upward growth of the leaf edges. The analytical levels found in leaves of plants growing on a complete nutrient solution and on solutions which nutrients had been excluded were respectively: N-4.24% and 3.61%; P-0.52% and 0.14%; K-3.81% and 1.36%; Ca-1.29% and 0.28%; Mg-0.65% and 0.17%.
Mineral nutrition of papaya tree (Carica papaya L.): III - symptomatology of macronutrient deficiency